Changes in macrofossil distribution and recent dinamics of Distichia muscoides peatlands in the Sierra Nevada del Cocuy, Colombia - Margarita María Valderrama; Daniela Buitrago; María Margarita Bedoya; Juan C. Benavides (Caldasia, 2017)
Peatlands are permanently flooded wetland ecosystems that accumulate organic matter, which is what makes them carbon sinks and resevoirs. Peatlands that are located in páramos help to maintain water balance in surrounding ecosystems and regulate the distribution of the water used by human communities. Currently, peatlands are affected by climate change, which disrupts the balance between plant production and decomposition. Peatlands dominated by Distichia muscoides are particularly important since they depend on glacial hydrology. This paper presents a climatic reconstruction over the last 200 years, based on the vegetation succession history recorded in core samples from two peatlands located in the Sierra Nevada del Cocuy. The reconstructed vegetation was compared with historical records of temperature and precipitation. Our results showed differences in the trajectories followed by the vegetation, with an increase in plant production and dominance of D. muscoides over the last two decades related to increases in temperature. The positive water balance generated by the global increase in temperature and glacial melting results in an abundance of vascular plants in the turbera. The effect of the El Niño event of 1998 is reflected in a major change in the trajectories of the vegetation at the two sites, with Sphagnum peat being replaced by peat formed from different mosses, limiting the ability of the peatland to store organic matter. The effects of climate change are multiplied by phenomena such as El Niño that can rapidly alter the evolution of an ecosystem, even one as highly resilient as peatlands.